Wood Polymer Nanocomposites Chemical Modifications, Properties and Sustainable Applications - Rahman, Md Rezaur; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book shows how chemical modifications influence some properties of wood nanocomposites. It describes suitable and effective chemical modifications that strengthen the physico-mechanical, thermal and morphological properties of wood. The authors provide intuitive explanation of the various types of chemical modifications applied to polymer cell walls in wood. They emphasize the reaction changes in wood cell walls due to the chemical modifications. Increased mechanical strength, improved thermal stability as well as the efficient retardancy against fungi attack are described. This book concludes summarizing the potential applications of wood-based nanocomposites taking into account sustainability and economic aspects.
Introduction and reinforcing potential various clay and monomers dispersed wood nanocomposites -- Preparation and characterizations of various clay and monomers dispersed wood nanocomposites -- Combined styrene/MMA/nanoclay cross-linker effect on wood-polymer nanocomposites -- Oxidation of wood species by sodium meta periodate and impregnation with phenyl hydrazine -- Characterization of N, N dimethylacetamid impregnated wood polymer nanocomposites -- Mechanical and thermal characterization of urea formaldehyde impregnated wood polymer nanocomposites -- Characterization of epoxy/nanoclay/wood polymer nanocomposites -- Influence of nanoclay/phenol formaldehyde resin on wood polymer nanocomposites -- Clay dispersed styrene-co-glycidyl methacrylate impregnated wood polymer nanocomposites: Impact on mechanical and morphological properties -- Physico-mechanical, morphological and thermal properties of clay dispersed styrene-co-maleic acid impregnated wood polymer nanocomposites -- Preparation andcharacterizations of clay dispersed styrene-co-ethylene glycol dimethyl acrylate impregnated wood polymer nanocomposites -- Evaluation of clay dispersed styrene-co-3-trimethyl silyl propyl methacrylate impregnated wood polymer nanocomposites on physical, mechanical, thermal and morphological properties -- Investigations on the physico-mechanical, thermal and morphological properties of nanoclay dispersed acrylonitrile-co-butyl methacrylate wood polymer nanocomposites -- Studies on the physical, mechanical, thermal and morphological properties of impregnated furfuryl alcohol-co-glycidyl methacrylate/nanoclay wood polymer nanocomposites -- Nanoclay dispersed furfuryl alcohol-co-ethyl methacrylate wood polymer nanocomposites: The enhancement on physico-mechanical and thermal properties -- Sustainable application of various monomer/clay dispersed wood polymer nanocomposites.
Keywords: Ceramic materials; Materials; Biogeography; Polymers; Ceramics; Materials Engineering; Biogeosciences; Polymers